Literature Review; Analisis Karakteristik Perawat Yang Dibutuhkan Guna Menunjang Tercapainya Kepuasan Pasien - Prasetyo, Taufan Agung; irawandi, dedi; Sustrami, Dya (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: Nurses in a health institution are important. Nurses are healthworkers who have the most direct interactions with patients, so the figure of agood nurse is certainly expected by patients or their families. In this case, theassessment of the figure of a good nurse is not only seen from her scientificability to provide nursing care, but also must pay attention to other factors,such as friendliness, appearance, and ways of communicating. Objectives: Thepurpose of this review literature is to analyze the characteristics of nursesneeded to support patient satisfaction. Methods: In writing this literaturereview, using the method of searching literature from international articlesusing the ScienceDirect, Goggle Scholar, and ProQuest databases. An initialsearch using keywords: